Conjugated Polymer Nanoparticles with Appended Photo‐Responsive Units for Controlled Drug Delivery, Release, and Imaging. Issue 40 (11th September 2018) - Senthilkumar, Thangaraj; Zhou, Lingyun; Gu, Qi; Liu, Libing; Lv, Fengting; Wang, Shu
Abstract: Carriers that can afford tunable physical and structural changes are envisioned to address critical issues in controlled drug delivery applications. Herein, photo‐responsive conjugated polymer nanoparticles (CPNs) functionalized with donor–acceptor Stenhouse adduct (DASA) and folic acid units for controlled drug delivery and imaging are reported. Upon visible‐light ( λ =550 nm) irradiation, CPNs simultaneously undergo structure, color, and polarity changes that release encapsulated drugs into the cells. The backbone of CPNs favors FRET to DASA units boosting their fluorescence. Notably, drug‐loaded CPNs exhibit excellent biocompatibility in the dark, indicating perfect control of the light trigger over drug release. Delivery of both hydrophilic and hydrophobic drugs with good loading efficiency was demonstrated. This strategy enables remotely controlled drug delivery with visible‐light irradiation, which sets an example for designing delivery vehicles for non‐invasive therapeutics. Abstract : Photo‐responsive nanoparticles are synthesized from a conjugated polymer (CPNs) by functionalization with Stenhouse adduct and folic acid units. Upon irradiation, CPNs undergo simultaneous structure, color, and polarity changes that release encapsulated drugs into the cells. This strategy enables remotely controlled drug delivery for non‐invasive therapeutics.